EFEKTIVITAS PENGGUNAAN TEKNIK EFFECTIVE QUESTIONING PADA MATA KULIAH IPA 1 UNTUK MENINGKATKAN KETERAMPILAN BERPIKIR TINGKAT TINGGI MAHASISWA - Ayu Rahayu; Retno Utaminingsih (SOSIOHUMANIORA: Jurnal Ilmiah Ilmu Sosial dan Humaniora, 2016)
This research aims to determine the effectiveness of effective questioning technique in IPA 1 subject in improving high order thinking skills of students. Besides that, the research aims to determine the improvement of high order thinking skills of students that follow the instruction based on effective questioning technique in IPA 1 subject. The research method used isquasi experimental research with control-group pre-test post-test design. The population of this research is students of Elementary School Teacher Education Department that attends IPA 1 subject in the academic year 2014/2015. Research sample determines by simple random sampling techniques with 50 students in experiment class and 47 students in control class. Technique of data analysis which is used in this research is test of high order thinking skills. Hypothesis testing method used is Mann Whitney test. The result showed that the effective questioning techniqueis effective to improve higher-order thinking skills of students. The improvement of high order thinking skills of students who follow the instruction based on effective questioning technique in IPA 1 subject is 88,03% with the effect size of the use of effective questioning technique in experiment class is 54,47%.Key words: effective questioning technique, high order thinking skillsÂ Â  , IPA 1